Comparison of prescribing indicators of academic versus non-academic specialist physicians in Urmia, Iran - Laya Sadigh-Rad; Leila Majdi; Mehrnush Javaezi; Mohammad Delirrad (Wolters Kluwer Medknow Publications, 2015)
Objective: As chief prescribers, physicians could have a key role in rational drug use. Core prescribing indicators of all physicians have been evaluated in the Islamic Republic of Iran for several years, but no study has assessed the effects of academic status of doctors on their prescribing behaviors. We aimed to compare prescribing indicators of two groups of academic and non-academic specialist physicians working in Urmia, Iran. Methods: In this cross-sectional study, prescribing indicators of the total number of 37 academic and 104 non-academic specialist physicians in six medical specialties (infectious diseases, psychiatry, otorhinolaryngology, gynecology, pediatrics and general surgery) were studied during 2012 using Rx-analyzer, a dedicated computer application. A set of five quality indicators was used based on the World Health Organization and International Network for Rational Use of Drugs recommendations. Findings: Totally, 709,771 medications in 269,660 prescriptions were studied. For academic and non-academic specialist physicians, the average number of medications per prescription was 2.26 and 2.65, respectively. Similarly, patients' encounters with injectable pharmaceuticals were 17.37% and 26.76%, respectively. The corresponding figures for antimicrobial agents were 33.12% and 45.46%, respectively. The average costs of every prescription were 6.53 and 3.30 United States Dollar for academic and non-academic specialist physicians, respectively. All the above-mentioned differences were statistically significant. Conclusion: Better prescribing patterns were observed in academic specialist physicians. However, they prescribed medications that were more expensive, while the reason was not investigated in this study. Further studies may reveal the exact causes of these differences.